Study of Landforms for The Manado-Tomohon Road Track - Selvana T.R. Tewal,; Sri Sulastriningsih,; Jolanda E. Kaihatu, (Technium Social Sciences Journal, 2023)
The Manado-Tomohon line is one of the main transportation routes connecting Manado City as the capital city of North Sulawesi Province with several regencies and cities such as Minahasa, Mitra, Tomohon City, and Bolsel Regency. The Manado-Tomohon route in terms of economic activity is quite high because there are motels, fruit, and snack trade routes, as well as residential areas. From the geological aspect, it is covered with less compact material and has a rough topography and high rainfall, where these physical factors are very influential on changes in landform/geomorphology on the Manado-Tomohon road track. Seeing this, it is very important to study and map the geomorphological condition of the Manado-Tomohon road track. The purpose of this research is to prepare a geomorphological map/landform and examine the geomorphological aspect/landform of the Manado-Tomohon road track.